Analisis Faktor Penyebab Stres Kerja dan Dampaknya pada Kinerja Karyawan Swasta Kota Samarinda di Masa Pandemi Covid-19 - Asmadhini Handayani Rahmah; Fitri Wardiani (Esensi: Jurnal Bisnis dan Manajemen, 2021)
The emergence of Covid-19 in Indonesia has a significant impact on various aspects, especially human resources. The emergence of work stress due to changes in work patterns can result in decreased employee performance. Therefore, the aims of this study is to determine the influence of internal and external factors of employees on work stress as an intervening variable, as well as its impact on performance directly and indirectly. The subject of the study was a private employee of Samarinda City. Research data collection method is a survey method with questionnaires, while the analysis tool used is path analysis. The results of the study were that partially, workload, Job Insecurity and job satisfaction had a significant influence on work stress, however, the work environment and individual characteristics had no significant effect on work stress, but were simultaneously significant. While external factors, internal and work stress have a significant influence partially and simultaneously on employee performance. Direct influence is the best model of influence for this study